The Relationship Between Patient Characteristics and Satisfaction with Pharmaceutical Services at Gamping 2 Sleman Community Health Center - Afrizal Syahyeri; Stefani Nuri Alvita; Niken Larasati (Indonesian Journal of Pharmacy and Natural Product, 2025)
Pharmacy services in community health centers are essential for directly interacting with patients and improving their quality of life related to medication use. Health centers must provide good services to achieve patient satisfaction. Factors like occupation, education, gender, and age may affect patient satisfaction levels. This study aims to explore the relationship between patient characteristics and satisfaction with pharmaceutical services at Gamping 2 Sleman Commmunity Health Center. The study used a cross-sectional approach and analytical observational method to identify relationships between variables. Data collection involved purposive sampling based on specific criteria. For analysis, the researchers applied the Kruskal-Wallis test. Most patients at Gamping 2 Sleman Community Health Center were aged 17 to 25 years (31%), female (74%), with an equal number of employed and unemployed patients (50% each). Most had secondary education (senior/vocational high school) (45%). Patient satisfaction was rated very high across all dimensions, with the highest percentage in the assurance dimension (81.20%) and the lowest in the responsiveness dimension (79.10%). The Kruskal-Wallis test indicated a significant relationship between age and satisfaction level (p = 0.023 < 0.05). However, no relationship was found between gender, education, or occupation and satisfaction level. In conclusion, age was significantly linked to satisfaction level, while gender, education, and occupation were not.